Answer:
Option B is correct.
[tex]3^{4}\times 9^{8}\times 3^{13}\times 9^{19}=3^{17}\times 9^{27}[/tex]
Step-by-step explanation:
Given:
The given expression is.
[tex]=3^{4}\times 9^{8}\times 3^{13}\times 9^{19}[/tex]
We need to simplify the given expression.
Solution:
The given expression as.
[tex]=3^{4}\times 9^{8}\times 3^{13}\times 9^{19}[/tex]
Rewrite the expression by shifting the term.
[tex]=3^{4}\times 3^{13}\times 9^{8}\times 9^{19}[/tex]
Using product rule [tex]x^{m}+x^{n}=x^{(m+n)}[/tex]
[tex]=3^{(4+13)}\times 9^{(8+19)}[/tex]
[tex]=3^{17}\times 9^{27}[/tex]
Therefore, option B is correct
[tex]3^{4}\times 9^{8}\times 3^{13}\times 9^{19}=3^{17}\times 9^{27}[/tex]